Petroleum reservoir modeling and simulation geology, geostatistics, and performance prediction - Srinivasan, Sanjay; Leung, Julianna (McGraw Hill, 2022)
Detailed reservoir engineering fundamentals and real-world applications along with well testing procedures This practical resource provides you with the tools and techniques you need to successfully construct petroleum reservoir models of all types and sizes. You will learn how to improve reserve estimations and make development decisions that will optimize well performance. Each chapter features detailed explanations and applications as well as examples and exercise questions that reinforce salient points. Petroleum Reservoir Modeling and Simulation: Geology, Geostatistics, and Performance Prediction describes the process of applying reservoir modeling techniques and flow analysis methods to specific geologic systems encountered in all subsurface exploration and development. Special attention is given to shale, carbonate, and subsea formations. You will get comprehensive coverage of geologic descriptions, quantitative modeling, geostatistics, well testing principles, upscaled models, and history matching. *Contains worked-out numerical examples and cases studies*Provides software simulation modules that demonstrate modeling and analysis*